Day 1 Tue, January 24, 2017 2017
DOI: 10.2118/184858-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of the Conductivity of Unpropped Fractures in Shales

Abstract: There is a great deal of evidence that shows that hydraulic fracturing creates a large surface area of induced unpropped (IU) fractures, that are too small to accommodate commonly used proppants and subsequently close during production (Sharma and Manchanda 2015). Due to their enormous surface area, IU fractures can play an important role in hydrocarbon production if they are allowed to remain open during production. Therefore, the conductivity of these IU fractures under different conditions of stress and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Wu et al 36 proposed a stress-sensitive equation obtained by experimental fitting to describe the impact of rock lithology on the conductivity of unsupported natural fractures. On this basis, Ashish Kumar et al 37 considered the effective stress of the induced complex fracture network and proposed a reservoir numerical model coupled with geo-mechanical effects to simulate the dynamic closure process of complex fracture networks, and the pressure drop strategy optimization plan was proposed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Wu et al 36 proposed a stress-sensitive equation obtained by experimental fitting to describe the impact of rock lithology on the conductivity of unsupported natural fractures. On this basis, Ashish Kumar et al 37 considered the effective stress of the induced complex fracture network and proposed a reservoir numerical model coupled with geo-mechanical effects to simulate the dynamic closure process of complex fracture networks, and the pressure drop strategy optimization plan was proposed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The final mass transfer stage is that the matrix pore structure changes with the effective stress, resulting in a decline in porosity and permeability, which affects long-term gas production of shale gas wells. To sum up, there are three specific production system mechanisms: (1) artificial fractures conductivity loss; (2) micro-fractures stress sensitivity; and (3) matrix stress sensitivity. …”
Section: Introductionmentioning
confidence: 99%
“…You et al studied the flow rule of nC8 in quartz pores under the condition of water film through molecular dynamics, and found that layered structures were formed on the surface of quartz pores and liquid-liquid slip occurred at the oil-water interface, revealing the migration mechanism of oil in quartz pores under the condition of water film (Zhou et al, 2017;Liu et al, 2019). By analyzing a variety of cationic surfactants, Yang et al studied their adsorption mechanism on the quartz surface and found that a double-layer structure was formed at the critical micelle concentration, indicating that the surfactant affected the properties of the cationic adsorption film on the quartz surface (Wu et al, 2017;Su et al, 2019;Hou, 2020). Wang et al investigated the flow pattern of oil-water two phases in calcite pores through molecular dynamics and found that liquid-liquid slip existed at the oil-water interface (Yang, 2016;You et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing a variety of cationic surfactants, Yang et al studied their adsorption mechanism on the quartz surface and found that a double-layer structure was formed at the critical micelle concentration, indicating that the surfactant affected the properties of the cationic adsorption film on the quartz surface (Wu et al, 2017;Su et al, 2019;Hou, 2020). Wang et al investigated the flow pattern of oil-water two phases in calcite pores through molecular dynamics and found that liquid-liquid slip existed at the oil-water interface (Yang, 2016;You et al, 2018). Tong et al used molecular dynamics to study the fluid behavior and flow in clay pores and concluded that the fluid properties in clay pores would affect the efficiency of oil recovery, indicating that diffusion, viscosity reduction and other factors are the main mechanisms affecting enhanced oil recovery (Tong et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%